PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN ONLINE MATA KULIAH ALJABAR LINEAR ELEMENTER - Sri Novia Martin; Meria Ultra Gusteti (Jurnal Riset Pendidikan Dasar Dan Karakter, 2020)
Because of Corona virus or Covid 19 has infected many people in various countries including Indonesia, The Ministry of Education and Culture of Indonesia made a policy of number 4 in 2020 for studying at home online. This is done to break the chain of spreading the Corona virus. Online learning poses its own challenges for many groups including lecturers and students. Various methods and online learning applications are carried out in order to achieve maximum learning objectives. Among these applications are Google classroom and Google meet video conference. The purpose of this study was to determine the perceptions of students in online learning. The subjects of this study were 9 students of the mathematics education study program who were taking elementary linear algebra courses. This research is qualitative research. Data were collected using a Likert scale questionnaire. Then the data were analyzed using 3 steps, namely data reduction, data presentation, and drawing conclusions. The results of this study were the most students thought that online learning using Google classrooms and Google meet video conversion was good in several aspects, namely ease of access to applications, the suitability of learning time, interactions between lecturers and students, independence and student activity, implementation of learning and clarity of learning materials.